Nurse-patient communication on the south Texas border: Negotiating language and cultural discordance during the COVID-19 pandemic - Gonzalez, Ariadne A.; Davis, Stuart (Frontiers in Communication, 2022)
Throughout the COVID-19 pandemic, medical professionals have experienced unforeseen and often under-discussed hurdles to meeting the surging demand for patient care. In particular, practitioners in under-resourced areas have faced enormous barriers when attempting to provide the swell in demand for patient care. Attempting to address these issues through the growing body of literature on patient communication during the COVID-19 pandemic, this article centers the work experiences of registered nurses serving on the frontlines of the South Texas-Mexico border of Laredo, Texas. Using a qualitative method of semi-structured and in-depth interviews with nurses working inside two COVID-19 hospital units, our thematic analysis reveals the work challenges generated by language discordance and cultural disparities experienced between travel nurses, patients, and their families and the added workload and work strain generated from the language and cultural barriers experienced by local bilingual nurses, tracking how during a global pandemic such barriers place material strain on nurses’ workload, especially regarding quality patient care.